2017
DOI: 10.1039/c7ra06087d
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and insecticidal assessment of some innovative heterocycles incorporating a thiadiazole moiety against the cotton leafworm, Spodoptera littoralis

Abstract: A new 2-cyano-N-(5-ethyl-1,3,4-thiadiazol-2-yl)acetamide was utilized as a versatile precursor for the synthesis of various heterocycles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 31 publications
0
25
0
Order By: Relevance
“…As a continuation of our interest in the chemistry of cyanoacetamide [20–22,31–37], N , N ′, N ″, N ‴‐(5,10,15,20‐tetraphenylporphyrin‐2,7,12,17‐tetrayl)tetrakis(2‐cyanoacetamide) ( 8 ) was achieved by heating compound 7 with cyanoacetic acid in presence of drops of acetic anhydride. The structure of 8 was elucidated by spectroscopic data.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As a continuation of our interest in the chemistry of cyanoacetamide [20–22,31–37], N , N ′, N ″, N ‴‐(5,10,15,20‐tetraphenylporphyrin‐2,7,12,17‐tetrayl)tetrakis(2‐cyanoacetamide) ( 8 ) was achieved by heating compound 7 with cyanoacetic acid in presence of drops of acetic anhydride. The structure of 8 was elucidated by spectroscopic data.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, cyanoacetamide derivatives are considered one of the most significant starting materials for the synthesis of different heterocyclic derivatives [20–22]. From these above facts and in continuation to our interest in developing an attractive, and alternative synthesis of mono(heteroaryl)tetraphenyl porphyrin through the reaction of β‐cyanoacetamide moiety in compound 8 with bifunctional reagents and evaluation of their biological activity as antitumor reagents.…”
Section: Introductionmentioning
confidence: 99%
“…A class of heterocyclic azo dyes is the thiazolylazo dye. Thiazoles are an important class of heterocyclic compounds which are related with many types of biological properties, probably by virtue of the -N=C-S− group, these include insecticidal, herbicidal, anti-oxidant, -bacterial, -convulsant and -inflammatory [29] [30] [31] [32] [33]. Thiazoles are readily capable of crossing cellular membranes owing to their better liposolubility, attributed to the presence of a sulphur atom [32].…”
Section: Introductionmentioning
confidence: 99%
“…Thiazoles are an important class of heterocyclic compounds which are related with many types of biological properties, probably by virtue of the -N=C-S− group, these include insecticidal, herbicidal, anti-oxidant, -bacterial, -convulsant and -inflammatory [29] [30] [31] [32] [33]. Thiazoles are readily capable of crossing cellular membranes owing to their better liposolubility, attributed to the presence of a sulphur atom [32]. The thiazole ring is present in several potent pharmacologically active molecules such as sulfathiazole (an antimicrobial drug), ritonavir (an antiretroviral drug) and abafungin (an antifungal drug) [34].…”
Section: Introductionmentioning
confidence: 99%
“…reported that introduction of a 1,3,4‐oxadiazole ring into target compounds could change their polarity, binding affinity with their receptor and flexibility, effectively enhancing their bioactivity . Furthermore, thiophene groups constitute a class of scaffold in bioactive molecules that are related to a variety of activities including antifungal, antimicrobial, insecticidal and herbicidal . Over the past few years, the synthesis and bioactivity of thiophene derivatives have attracted considerable attention and some representative examples of thiophene‐derived compounds are known for their ability to protect certain plants against severe diseases …”
Section: Introductionmentioning
confidence: 99%